Pengembangan roti berbahan pati jagung dengan modifikasi enzimatis & pemanas ohmik (Kajian: pengaruh variasi tegangan dan transglutaminase terhadap karakteristik produk) [Development of corn starch-based bread with enzymatic modification & ohmic heating: study effect of voltage and transglutaminase variations on product characteristics] - Hutasoit, Jenri Parlinggoman; Ariskanopitasari, Ariskanopitasari; Khamidah, Aniswatul (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
The main challenges in producing gluten-free bread are closely related to its development, texture, and nutrition. This research consisted of 2 stages. Stage 1 was aimed to determine the effect of voltage variations (70 V, 80 V, 90 V, 100 V, 110 V, 120 V, and conventional baking as a control) on bread characteristics and process parameters. The experiment was arranged as non-factorial in a completely randomized design with 3 replications. The best results of the first stage were applied in stage 2, aimed to determine the effect of various concentrations of TGase (0, 0.5, 1, 1.5, 2, and 2.5%). The data were processed using analysis of variance, then further tested using Tukey's at the 5% level. The 120 V voltage gradient treatment was found to be the best treatment. It shows specific volume 3.17±0.17 cm3/g, baking loss 14.58±1.50%, brightness 50.97±3.27, hardness 3.76±0.11, cohesive 0.34±0.03, pore density 84±2.52. In addition, baking at a higher voltage level increased the temperature rate and electrical conductivity. The 120 V voltage treatment shows the time required to reach a maximum temperature of 97°C was 3 minutes 5 seconds, and an electrical conductivity value of 0.26-0.51 S/m. Based on the TGase treatment, it was found that when bread dough was applied with a higher TGase concentration, the specific volume, hardness, chewiness, resilience, cohesiveness and springiness, average pore size, and pore porosity of the bread increased.